Optimized method for determination of amoxicillin, ampicillin, sulfamethoxazole, and sulfacetamide in animal feed by micellar electrokinetic capillary chromatography and comparison with high-performance liquid chromatography - Injac, Rade (Array, 2009)
Summary: Antibiotics as additives in animal feedstuffs are forbidden in many countries in the world, but they are still abused. A micellar electrokinetic capillary chromatography method was performed at 25 °C and 30 kV (under pressure 15 mbar) using 25 mmol dm–3 phosphate buffer (pH = 8.0) containing 70 mmol dm–3 sodium dodecysulfate (SDS) and 10 % (volume fraction) methanol as the background electrolyte for separation and determination of amoxicillin, ampicillin, sulfamethoxazole, and sulfacetamide. UV detection was set at 210 nm. The method was validated and antibiotics were quantitatively determined as additives in spiked animal feedstuffs. Results were compared with a new HPLC method for the evaluation of four antibiotics in real samples. Both developed methods can be used for routine analysis of amoxicillin, ampicillin, sulfamethoxazole, and sulfacetamide as additives in animal feedstuffs